AKR1B10 as a novel prognostic biomarker linking methylation and immune escape in hepatocellular carcinoma - Muhammad Naveed Khan; Mao Binli; Hu Juan; Shi Mengjia; Wang Shunyao; Xiaosong Li (Discover Oncology)
Abstract Objective Liver cancer continues to be a significant challenge among malignancies today. Hepatocellular carcinoma is one of the cancers that exhibits a marked upregulation of AKR1B10, an enzyme involved in cellular metabolism. The advancement of HCC treatment indicates that immunotherapy and molecular targeted therapies exhibit potential efficacy. However, the primary targets for liver cancer are not yet well-defined. Therefore, this study investigates the mechanism of AKR1B10 to assess its potential as a prognostic biomarker in liver cancer. Methods Genetic changes, genomic expression, and methylation analyses were sourced from the TCGA, CPTAC, UALCAN, HPA, cBioPortal, and MethSurv databases. The gene expression is validated by qPCR. The diagnostic and prognostic significance of AKR1B10 in LIHC was assessed using data from ROC analysis and KM-plotter. Functional analyses were performed utilizing the GeneMANIA and STRING databases, along with gene-gene and PPI networks, GO terms, and KEGG pathway analyses. The relationship with immune escape was explored through analyses conducted using the TIMER, TISIDB, and GEPIA databases. Additionally, GSCALite was utilized to analyze drug sensitivity in relation to AKR1B10 expression in tumors. Results AKR1B10 expression was found to be statistically significantly higher in HCC cells than in their corresponding normal control cells, according to qPCR analysis. ROC analysis identified AKR1B10 as a novel biomarker for diagnosing LIHC. Univariate Cox regression analysis indicated AKR1B10 association with poor LIHC patient prognosis. Integrative analyses, including genetic alterations, gene-gene interactions, PPI networks, and enrichment analyses, support a novel role for AKR1B10 in HCC progression. Hypermethylation of AKR1B10 at various CpG sites was associated with improved or diminished OS in LIHC, and AKR1B10 exhibited a robust correlation with the top 25 genes that were either hypo- or hypermethylated. Furthermore, the findings indicated that AKR1B10 may affect the TME and is associated with immune checkpoints. Conclusions This study’s comprehensive analyses indicate AKR1B10 as a novel biomarker for LIHC.